(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This article provides an in-depth analysis of the current state of irrigated lands in the Fergana region and scientifically examines their natural-climatic, technical-meliorative, and ecological characteristics. The study revealed an increase in the need for water resources under conditions of the length of the growing season, low precipitation, and high temperatures. It was also noted that the soil cover is prone to salinization, the groundwater level is close to the surface, and the melioration systems are in a faulty state. When analyzing the technical condition of irrigation systems, it was found that most of the main and internal canals are physically obsolete, more than 60% of pumping stations require repair, and up to 30-40% of water is lost. In conditions where traditional irrigation methods prevail, the introduction of water-saving technologies is indicated as a pressing issue. The prevalence of erosion processes was assessed using the RUSLE model, NDVI, BSI indices, and topographic maps. According to the results, water erosion covered up to 20% of the area, and the rate of soil loss was 15-50 tons/ha/year. This led to a decrease in yield by an average of 10-15%. At the end of the study, recommendations were developed for a set of measures to restore the stability and fertility of irrigated lands, including the modernization of infrastructure, the introduction of digital monitoring systems, the expansion of water-saving technologies, and the application of anti-erosion agrotechnical measures.